Influence of cutting edge on core loss induced through various manufacturing parameters - Schneider, Michael; Hubert, Markus; Franke, Jörg (2016 6th International Electric Drives Production Conference, EDPC 2016 - Proceedings, 2016)
Various manufacturing processes in the production-from laminated magnetic steel sheets to an assembled stator-affect the electromagnetic characteristics. Often the manufacturing processes of the process step cutting are compared to highlight differences. Many publications have already dealt with this issue over several decades. Flux distribution, loss and the B-H characteristics are not the same, whether an electrical sheet with defined geometry is cut with a laser, water jet, electrical discharge machining, rotational cutting or with a punching machine. It is adequately researched that differences in loss behavior occur. Within the various technologies, a comparison of varied production parameters is scarcer. Here, interesting studies result when considering the specific hysteresis and eddy current losses in the variation of the process parameters on the relative position of the rolling direction, average speed, distance energy and the comparison between fiber and CO2-Laser with different focus diameters. This paper deals with the comparison of cut sheets made from electrical steel with grade M270 35A. The metal strips investigated were prepared on dimensions of 150×150 mm and 37,5×150 mm using the above parameter variation and analyzed in a single sheet tester from Brockhaus regarding their loss behavior.
CRIS-Team Scopus Importer:2023-03-07
Keywords: cutting; iron losses; measurement; sheet metal